CMZoom: Survey overview and first data release - Battersby, Cara; Keto, Eric; Walker, Daniel; Barnes, Ashley; Callanan, Daniel; Ginsburg, Adam; Hatchfield, H. Perry; Henshaw, Jonathan; Kauffmann, Jens; Kruijssen, Diederik; Longmore, Steven N.; Lu, Xing; et al. (The astrophysical journal. Supplement series, 2020)
We present an overview of the CMZoom survey and its first data release. CMZoom is the first blind, high-resolution survey of the Central Molecular Zone (CMZ; the inner 500 pc of the Milky Way) at wavelengths sensitive to the pre-cursors of high-mass stars. CMZoom is a 550 hr Large Program on the Submillimeter Array that mapped at 1.3 mm all of the gas and dust in the CMZ above a molecular hydrogen column density of 1023 cm−2 at a resolution of ∼3″ (0.1 pc). In this paper, we focus on the 1.3 mm dust continuum and its data release, but also describe CMZoom spectral line data which will be released in a forthcoming publication. While CMZoom detected many regions with rich and complex substructure, its key result is an overall deficit in compact substructures on 0.1-2 pc scales (the compact dense gas fraction: CDGF). In comparison with clouds in the Galactic disk, the CDGF in the CMZ is substantially lower, despite having much higher average column densities. CMZ clouds with high CDGFs are well-known sites of active star formation. The inability of most gas in the CMZ to form compact substructures is likely responsible for the dearth of star formation in the CMZ, surprising considering its high density. The factors responsible for the low CDGF are not yet understood but are plausibly due to the extreme environment of the CMZ, having far-reaching ramifications for our understanding of the star formation process across the cosmos.
Gesehen am 29.09.2020